Social movements in defense of public water services: the case of Spain - Berge, Jerry van den; Scheunpflug, Luca; Vos, Jeroen; Boelens, Rutgerd (Frontiers in Water, 2023)
In several cities and regions in Spain there has been a fight against privatization of water supply in the past decade. Some cities have decided to re-municipalise water supply and debates about implementing the human right to water and sanitation have been held in many parts of Spain, following the success of the Right2Water European Citizens’ Initiative. This paper examines how the European “Right2Water” movement influenced struggles for access to and control over water in Spain from a political ecology perspective. It explores how “Right2Water” fuelled the debate on privatization and remunicipalisation of water services and what heritage it has left in Spain. We unfold relationships with and between water movements in Spain – like the Red Agua Publica – and relationships with other networks – like the indignados movement and subsequently how water protests converged with austerity protests. In different places these struggles took different shapes. By deploying five case studies (Madrid, Valladolid, Terrassa, Barcelona and Andalucía), we look at how the human right to water and sanitation framework served as a tool for social and water justice movements. Struggles for water justice in Spain are ongoing and we seek to identify the temporarily outcomes of these struggles, and whether power balances in Spain’s water services provision have shifted in the past decade.